Pharmacists’ knowledge and counselling on fall risk increasing drugs in a tertiary teaching hospital in Nigeria (2020)
Background: Falls and fall-related injuries are a foremost health concern among older adults aged 60 years and above. Fall-risk-increasing drugs (FRIDs) use by older adults is one related cause of falling, and it is frequently used among older adults. Pharmacist-led counselling is an aspect of patient education that has been associated with improved therapeutic outcome and quality of life in high income countries with scarcity of information in lowmiddle income countries. This study therefore aims to assess hospital pharmacists’ knowledge and counselling on fall-related medications using the list compiled by the Swedish National Board of Health and Welfare on FRIDs and orthostatic drugs (ODs). Methods: A cross-sectional survey was carried out among 56 pharmacists working in a teaching hospital in Nigeria, between July and August 2019, using a self-administered questionnaire. Data were summarized with descriptive statistics while chi-square test was used for categorical variables at p < 0.05. Results: Thirty-five (62.5%) were within 10 years of practice experience. Two-third (62.5%) of the pharmacists possessed an additional qualification to Bachelor of Pharmacy degree. Twenty-two (40.0%) were aware of the FRIDs and ODs list. In all, (89.3%) had “unsatisfactory” knowledge of classes of medications and specific medicines that could cause a fall. Most pharmacists 42 (80.8%) focused counsel on appropriate medication use, adverse effects of drugs and storage of medications. Knowledge score of both FRIDs and ODs were neither significantly associated with pharmacists’ years of qualification (χ 2 = 1.282; p = 0.733), (χ 2 = 2.311; p = 0.510) nor with possession of additional qualification (χ 2 = 0.854; p = 0.836), (χ 2 = 2.996; p = 0.392). Majority, 53 (98.1%) believed that patients will benefit from effective counselling on FRIDs and ODs. About half (25; 51.0%) suggested training through seminar presentation as a measure for FRIDs and ODs sensitization. Conclusion: A substantial gap in knowledge and awareness of FRIDs and ODs was noted among the hospital pharmacists. However, engagement of pharmacists on counsel that focus on medication use, adverse effect and storage was relatively better. Thus, there is a general need to create awareness about fall-risk-increasing drugs among hospital pharmacists, so as to help improve the therapeutic outcome particularly in the older adults.